Selection of appropriate analytical tools to determine the potency and bioactivity of antibiotics and antibiotic resistance - Nishant A. Dafale; Uttam P. Semwal; Rupak K. Rajput; G.N. Singh (Elsevier, 2016)
Antibiotics are the chemotherapeutic agents that kill or inhibit the pathogenic microorganisms. Resistance of microorganism to antibiotics is a growing problem around the world due to indiscriminate and irrational use of antibiotics. In order to overcome the resistance problem and to safely use antibiotics, the correct measurement of potency and bioactivity of antibiotics is essential. Microbiological assay and high performance liquid chromatography (HPLC) method are used to quantify the potency of antibiotics. HPLC method is commonly used for the quantification of potency of antibiotics, but unable to determine the bioactivity; whereas microbiological assay estimates both potency and bioactivity of antibiotics. Additionally, bioassay is used to estimate the effective dose against antibiotic resistant microbes. Simultaneously, microbiological assay addresses the several parameters such as minimal inhibitory concentration (MIC), minimum bactericidal concentration (MBC), mutation prevention concentration (MPC) and critical concentration (Ccr) which are used to describe the potency in a more informative way. Microbiological assay is a simple, sensitive, precise and cost effective method which gives reproducible results similar to HPLC. However, the HPLC cannot be a complete substitute for microbiological assay and both methods have their own significance to obtain more realistic and precise results.